ASSESSMENT OF THE GENERAL CONDITION AND QUALITY OF LIFE OF WOMEN POST-PRODUCTIVE AGE, WHO SUFFERED FROM COVID-19 ASYMPTOMATICALLY, AND 12 MONTHS AFTER THE MODERATE SEVERE FORM OF THE DISEASE (Spectrum Journal of Innovation, Reforms and Development, 2022)
Assessment of the general condition, laboratory parameters, and quality of life of post-productive women after the asymptomatic course of COVID-19 and 12 months after the moderate course of the disease.